TEORI BELAJAR ELABORASI (SUATU STRATEGI PEMBELAJARAN) - Rohman, Fatkhur (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2019)
This brief paper will elaborate on the theory of learning elaboration and elaboration learning proposed by Charles M Reigeluth and Stein (1983) using seven components of strategy, namely the elaborative sequence, the prerequisite sequence of learning (within each subject), summarizer (summary), synthesizer (synthesis),Analogy, Cognitive Strategy Activator (activating cognitive strategies), and learning control.